Permeation properties of light hydrocarbons through TS 1 membrane - Dung, Cong Tien; Fila, Vlastimil; Thao, Phuong; Thuan, Ngo Thi (Vietnam Journal of Chemistry, 2015)
The work presents permeation and separation characteristics of Titanosilicate (TS‑1) membrane measured for single components and equimolar binary mixtures such as ethane/methane, propane/methane, n‑butane/methane and n‑butane/isobutane. TS‑1 membrane was prepared on stainless steel support using the secondary crystal growth technique. The thickness of composite TS‑1 membrane was about 8 μm. From the single component characteristics of TS‑1 membrane, the highest flux was observed for ethane. In the case of binary mixture separation, the separation factors measured at 50 °C were 24 (n‑butane/methane), 19 (propane/methane) and 6 (ethane/methane) with the fluxes in the range from 3 to 21 mmol.m-2.s-1 confirming preparation of high quality TS‑1 membrane. Keywords. TS‑1 membrane, gas separation, MFI membrane, light hydrocarbon.